Mechanical properties of treated arenga pinnata fibre reinforced nanomodified epoxy composite / Muhamad Faris Syafiq Khalid - Syafiq Khalid, Muhamad Faris (2017)
Natural fibres have attracted researchers and manufacturers attention due to their num erou s adva ntages such as abunda nce of resources, environmental friendly, less harm to human body, good mechanical properties and low density. In order to increase the usage of natural fibre , lot s of researches have bee n don e on natura l fibres as re info rceme nt to polymer matrix. In this study, plant base d natu ral fibre ca lled Arenga Pinnata was se lec ted and its properties were studied. Arenga Pinn ata fibre was se lec ted due to its remarkable characteristic s especially high dura bi lity and resistance to sea wate r. Foc us of thi s study is to evaluate the effect of fibre vo lume frac tion , fill er incl usio n and fibr e surface treatm ent on phy sical and mec han ica l prop erties of Arenga Pinn ata fibr e reinforced epoxy composite (AP REC) . Mec hanica l properties of natur al fibr e re inforced polymer (NFRP) mostl y depend on the fib re and polymer prop erti es and also interfacial bond ing in betw een them. Th us, nanos ilica was used to enhance the mechan ical prop erti es of epoxy matrix and Are nga Pinn ata had been treated using silane in or der to impr ove interfacial bonding between fibres and matrix. The APREC samples, with 10vol%, 15vol%, 20vol%, and 25vo l% fibre vo lume fractio ns, were produ ced usin g hand -layup and cold-pre ssing techniques . Flex ura l, tensi le and compress ion tests were performed in order to obtai n modu lus of elas ticity , strength and strai n to failure of APREC. The morpho logical struct ure of fracture d speci mens was obse rve d usin g scanning electron microscopy (SEM) in order to eva luate the frac ture mechanisms involved . Preliminary tests were conducted on both unid ire ction al (UD) and rand om ori entation AP REC. Based on the result s, the perform an ce of UD APREC was better than random orientation APREC. The flexur al modulus and strength of UD APREC were 5.31% and 35 .73% higher than those of random APREC, res pec tive ly. There fore , UD APREC was se lecte d and used for eva lua tion of the effec t of fibr e vo lume fraction , filler incl usion and fibre surface trea tme nt. The res ults show ed that nanosili ca additi on and silane treatment improved mechani cal prop erti es of UD APREC. Flexural modulus and strength of UD APREC was increased by 5.42 1Yo and 3.59% with addition of 5wt% nanosilica, 8.53% and 13.25% with silane treatm ent , and 15.46% and 13.75% with both , respec tive ly . Nanos ilica addition and si lane treatm ent showed positi ve improvement to UD APREC on tensile behaviour whe re ten sile modulus incre ased by 2.45%, 1.67%, and 3.34% for the addition of nanosil ica, silane treatm ent , and both procedure , respec tive ly . The additio n of 5wt% nanosili ca in silane- treated UD AP REC exhibited the highest ten si le strength where the incre me nt of 4.86% was observed compared to pur e UD APREC. Nanosi lica addition gave the best impr ovement on compression prop ert ies of UD APREC compare d to flexural and ten sile properties when the compress ive modulus of UD APREC with nan osili ca addition shown 46 .6 1% increme nt, meanwhil e maximum compressive strength wa s obtai ned by UD APREC with addition of nanosili ca and silane treated fibre which gave 5.92% incre ment. Overall resu lts for th is study ind ica ted that the addition of 5% nanosilica and the used of silane treated fibr es give the best mechan ical properties of APREC. It can be concl uded th at the addition of nanosilic a and silane trea tment on Arenga Pinn ata fib res enhanced the flexur al, tensile, and compress ive properties of UD APRE